A meta-analysis of MHC diversity in Pan troglodytes verus - Christelle Vangenot; Alicia Sanchez‑Mazas (Revue de Primatologie)
We performed a meta-analysis of the Major Histocompatibility Complex (MHC) diversity for locus A, B, C, DQB1, DPB1 and DRB1 in Chimpanzees by selecting cohorts of animals for which MHC genotypes were available in publications and by extracting DNA sequences available on the IPD-MHC database. The MHC genes play a key role in the immune responses and are located on the short arm of chromosome 6. In humans, this system, also called HLA, is one of the most polymorphic regions of the genome and is consequently very informative to study peopling history. The MHC region has been subdivided in different classes according to the functional and structural characteristics of the genes. For Class I, chimpanzees possess single A, B and C loci orthologous to the human MHC loci A, B and C, respectively. They also possess an additional class I locus, AL, with low polymorphism, poorly expressed and found only on the haplotypes of 50% of Pan troglodytes individuals and not observed in Pan paniscus. As AL sequences are very similar to chimpanzee and human A sequences, this locus is estimated to have diverged from A more than 20 mya (Adams and Parham, Species-specific evolution of MHC class I genes in the higher primates, Immunol Rev, 2001, 183: 41-64). The Class II region is subdivided into DR, DQ and DP loci each containing A and B genes. The DR locus of catarrhines may display allelic polymorphism, configuration polymorphism and gene-related transcription levels (Doxiadis et al., DR haplotype diversity of the cynomolgus macaque as defined by its transcriptome, Immunogenetics, 2012, 64: 31-37). Different numbers and/or combinations of DRB genes have been defined: human DRB has five configurations with DRB1 displaying abundant allelic variation; chimpanzees have nine configurations with or without DRB1 and moderate allelic variation. Like in humans, the DQ locus of chimpanzees contains two sets of gene pairs: DQA1-DQB1 and DQA2-DQB2. In chimpanzees both DQA1 and DQB1 are polymorphic (Bontrop et al., Comparative genetics of MHC polymorphisms in different primate species: Duplications and deletions, Hum Immunol, 2006, 67: 388-397) with DQA1 lineages shared between humans and chimpanzees. Similarly, the DP locus contains two sets of gene pairs: DPA1-DPB1 and DPA2-DPB2 but the latter are inactive. The region is similar in humans and chimpanzees and is stable (Bontrop et al., 2006). In the present study, we analyze the MHC molecular diversity in Chimpanzees at six different loci based on all data currently available on the IPD-MHC database and we discuss the results in relation to human HLA variation. In addition, we investigate which peculiar evolutionary forces could have acted at different loci given the genetic profile observed in populations. This gives us an original focus on MHC evolution and its mechanisms and helps us to understand the specificities of the human and chimpanzee lineages, respectively.